2017
DOI: 10.1016/j.jcrs.2017.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging to assess neuroadaptation to multifocal intraocular lenses

Abstract: Neuroadaptation to multifocal IOLs took place initially through recruitment of visual attentional and procedural learning networks. Thereafter, a form of long-term adaptation/functional plasticity occurred, leading to brain activity regularization toward a non-effort pattern. These findings, which reinforce the crucial role of higher-level brain regions in the perceptual construction of vision, were consistent with functional and questionnaire outcomes and were unrelated to optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 14 publications
4
55
0
1
Order By: Relevance
“…The study published by Kretz et al [21] demonstrated that binocular implantation of diffractive trifocal IOLs (AtLisa tri 839 MP) provides significant VA improvement for all distances and fully functional vision including functional stereopsis, as compared to monocular visual outcome. The 12-month follow-up (longer than in other studies) and longer neuroadaptation time may have contributed to superior CS results in our study [22][23][24][25][26]. Besides neuroadaptation, the other possible explanation for better near CS outcome in AtLisa tri 839 MP group might be major vergence dependence of this IOL as described by Esteve-Taboada [26].…”
Section: Discussionmentioning
confidence: 58%
“…The study published by Kretz et al [21] demonstrated that binocular implantation of diffractive trifocal IOLs (AtLisa tri 839 MP) provides significant VA improvement for all distances and fully functional vision including functional stereopsis, as compared to monocular visual outcome. The 12-month follow-up (longer than in other studies) and longer neuroadaptation time may have contributed to superior CS results in our study [22][23][24][25][26]. Besides neuroadaptation, the other possible explanation for better near CS outcome in AtLisa tri 839 MP group might be major vergence dependence of this IOL as described by Esteve-Taboada [26].…”
Section: Discussionmentioning
confidence: 58%
“…One recent investigation suggested that there is no correlation between the optical properties of an IOL (including total or high-order aberrations) and QoV scores [53]. Patients reporting dysphotic symptoms had increased activity in several regions of the frontoparietal circuits of the brain, including the cingulate gyrus and caudate nucleus [53,54]. Thus, particularly in the field of presbyopia correction, PROs might be of exceptional importantance.…”
Section: Importance Of Prosmentioning
confidence: 99%
“…It is unclear whether any of these myopia control methods may have caused long-term or sustained changes in visual function, although the visual system has been shown to adapt to changes in the optics of the eye over time. 37 40 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally some form of neuroadaptation may occur during DIMS wear, which compensates for optical deficiencies in the retinal image. 37 40 Although advantageous during DIMS wear, this adaptation might degrade visual performance. The current study therefore aimed to compare the 2-year changes in visual function in myopic children who normally wore either DIMS lenses or regular SV spectacle lenses to determine whether wearing DIMS lenses results in a change in visual function.…”
Section: Introductionmentioning
confidence: 99%